The Urgency of Artificial Intelligence Regulation in Indonesia’s Criminal Justice - Tertibi, Yaoma (Jayapangus Press, 2025)
The rapid development of artificial intelligence (AI) in criminal justice systems presents both opportunities and challenges, particularly regarding ethics, transparency, and accountability. This study aims to analyze the urgency of regulating AI in Indonesia’s criminal justice system. Using a normative-analytical approach, the research explores the risks of algorithmic bias, data privacy violations, and the absence of human oversight in legal decision-making. Comparative analysis with AI regulations in the European Union and the United States highlights key regulatory gaps in Indonesia. The findings reveal that without clear and enforceable legal frameworks, AI implementation may worsen legal inequalities and undermine human rights. This study underscores the need for a national legal framework that ensures algorithmic transparency, data protection, and human involvement in AI-driven decisions. The research offers an early contribution to the development of responsible and equitable AI governance in the justice sector.